Pengaruh Edible Coating terhadap Stabilitas Warna Resin Akrilik - Hertiana, Elin; Anita; Puspitadewi, Susi R. (e-GiGi, 2025)
Abstract: Disadvantages of heat-polymerized acrylic resin as a denture base material are porosity and water absorption, which can cause aesthetic problems due to causing discoloration of the acrylic resin. Color pigments in food or beverages can be absorbed into the acrylic resin, causing discoloration. This disadvantage may be prevented by a coating material such as an edible coating. This study aimed to determine the effect of edible coating on the color stability of acrylic resin. This was a laboratory and experimental study with a pretest-posttest control group design. Samples were 30 plates of acrylic resin measuring 10 x10 x 2 mm, divided into six groups, consisting of three groups without edible coating and three groups with edible coating. All were immersed in lemongrass water for three days, five days, and seven days. Color measurements of value, chroma, and hue were taken using the VITA EasyshadeÒ spectrophotometer. The result showed there were significant color differences in chroma and hue values after immersion in lemongrass water for seven days (p=0.045 and p=0.028). In conclusion, acrylic resin with edible coating has better color stability compared to acrylic resin without edible coating. Keywords: acrylic resin; dentures; edible coating; color stability    Abstrak: Kekurangan resin akrilik polimerisasi panas sebagai bahan basis gigi tiruan ialah porositas dan penyerapan air yang dapat menimbulkan masalah estetik karena mengakibatkan perubahan warna pada resin akrilik.  Zat warna dalam makanan atau minuman yang dikonsumsi dapat terserap ke dalam resin akrilik sehingga terjadi perubahan warna. Kekurangan ini mungkin dapat dicegah oleh bahan pelapis seperti edible coating. Penelitian ini bertujuan untuk mengetahui pengaruh edible coating terhadap stabilitas warna resin akrilik. Jenis penelitian ialah eksperimental laboratorik dengan desain pretest-posttest with control group. Sampel penelitian ialah 30 buah resin akrilik berukuran 10 x 10 x 2 mm, dibagi menjadi enam kelompok yaitu tiga kelompok tanpa edible coating dan tiga kelompok dilapisi edible coating, dan semuanya direndam dalam air rebusan serai dapur selama tiga hari, lima hari, dan tujuh hari. Pengukuran warna value, chroma dan hue menggunakan alat spektrofotometer VITA EasyshadeÒ. Hasil penelitian mendapatkan perbedaan warna yang bermakna pada nilai chroma dan hue setelah perendaman selama tujuh hari (p=0,045 dan p=0,028). Simpulan penelitian ini ialah resin akrilik yang dilapisi edible coating memiliki stabilitas warna yang lebih baik dibandingkan dengan resin akrilik tanpa edible coating. Kata kunci: resin akrilik; gigi tiruan; edible coating; stabilitas warna